Wybrane problemy wprowadzania przedsiębiorstw na Giełdę Papierów Wartościowych w kontekście wzrostu efektywności ich działania oraz maksymalizacji wartości - Białowąs, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The author described chosen aspects of Polish stock market functioning and showed history of stock market development. In the text, it is possible to read how many tasks companies have to implement in order to be noticed on stock market. In the end, the author of the article focused on correlation between process of moving on stock market and internal efficiency and value of factories. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 22-32